Effect of machining parameters and cutting tool coating on hole quality in dry drilling of fibre metal laminates. (15th March 2019) - Giasin, K.; Gorey, G.; Byrne, C.; Sinke, J.; Brousseau, E.
Abstract: Fibre metal laminates (FMLs) are a special type of hybrid materials, which consist of sheets of metallic alloys and prepregs of composite layers stacked together in an alternating sequence and bonded together either mechanically using micro hooks or thermally using adhesive epoxies. The present paper contributes to the current literature by studying the effects of three types of cutting tool coatings namely TiAlN, AlTiN/TiAlN and TiN on the surface roughness and burr formation of holes drilled in an FML commercially known as GLARE®. While the cutting tool geometry is fixed, the study is also conducted for a range of drilling conditions by varying the spindle speed and the feed rate. The obtained results indicate that the spindle speed and the type of cutting tool coating had the most significant influence on the achieved surface roughness metrics, while tool coating had the most significant effect on burr height and burr root thickness. The most important outcome for practitioners is that the best results in terms of minimum roughness and burr formation were obtained for the TiN coated drills. However, such drills outperform the other two types of tools, i.e. with TiAlN and AlTiN/TiAlN coatings, only when used for short series of hole drilling due to rapid tool deterioration.